2018
DOI: 10.14746/sr.2018.2.1.06
|View full text |Cite
|
Sign up to set email alerts
|

Gender Construction in Sports, Family Habitus and “Gender Regime”

Abstract: Abstract:This article is based on data collected during a qualitative research on children's leisure practices and family socialization patterns. The paper focuses more specifically on the cross effects of gender and social class on the construction of body hexis and relationship to sports. The results show that several dimensions of family habitus must be taken into account: lifestyles, way in which parents divide the tasks of raising children and the relationship they have with social competition or gender n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…Our findings likewise indicate that school sport sailing in both Western France and California reproduced embodied gendered hierarchies and symbolic “regimes” of differentiation as manifested in power relations and divisions of work/roles (Mennesson and Forté, 2018). In both school sport sites, sailing abilities held gendered connotations in line with masculine forms of domination found in broader sailing culture where physical and intellectual skills related to trip preparation, tactical decision-making, toughness and problem-solving are often associated with masculine participation and values (Créac’h, 2003; Pociello, 1999; Vigarello, 1988).…”
Section: Discussion: Gendered Regimes Found In School-based Light Saisupporting
confidence: 59%
See 1 more Smart Citation
“…Our findings likewise indicate that school sport sailing in both Western France and California reproduced embodied gendered hierarchies and symbolic “regimes” of differentiation as manifested in power relations and divisions of work/roles (Mennesson and Forté, 2018). In both school sport sites, sailing abilities held gendered connotations in line with masculine forms of domination found in broader sailing culture where physical and intellectual skills related to trip preparation, tactical decision-making, toughness and problem-solving are often associated with masculine participation and values (Créac’h, 2003; Pociello, 1999; Vigarello, 1988).…”
Section: Discussion: Gendered Regimes Found In School-based Light Saisupporting
confidence: 59%
“…(Brown, 2006: 170, emphasis ours) Since sailing has been naturalised as a male dominated activity due to deep-rooted yet dehistoricised somatic codes, we wanted to examine how young men and women participants were distinguished and came to exist within school sailing's gender regimes. This involved analysing how everyday power relations, social interactions and divisions of work/roles underpinned the constitution of gendered relationships and hierarchies (Connell, 2002;Mennesson and Forté, 2018).…”
Section: Bourdieu and The Gendered Practices Of Sailingmentioning
confidence: 99%
“…French adults, usually steeped in the local ocean culture and sailing practice themselves, were typically more culturally and aesthetically focused under this perspective of cultural capital acquisition. The French findings resonate with Mennesson and Forté’s study (2018), which likewise examined how dominant class French families prioritised the acquisition of a “family habitus” reflecting the transmission of a “cultured lifestyle” through physical activities that can provide high social and academic status. This French cultural reproduction practice does not typically involve the “expression of an ability to surpass others” through competitive sports (Mennesson and Forté, 2018: 104).…”
Section: Discussionmentioning
confidence: 58%
“…It has likewise been found that the social class positioning of one's family influences youths' actual sporting experiences and engagements (Wright and O'Flynn, 2007). A body of research reveals that parents, in particular, reproduce certain ideologies and practices during the course of sports parenting based upon their own social class positioning (Atencio et al, 2018;Coakley, 2006;Dagkas and Quarmby, 2015;Friedman, 2013;Karp, 2010;Mennesson and Forté, 2018;Messner, 2009). Thus, particularly within the context of neo-liberal Western societies, parents play a vital role in transmitting certain beliefs and values regarding sport and physical activity as part of youths' socialisation; crucially, upper class families rather than low-income ones will have more resources to support and make choices regarding their children's sport and physical activity participation (Quarmby and Dagkas, 2010).…”
Section: Adult Intervention In School Sport and Sailingmentioning
confidence: 99%